Mediating the impact of academic migration on student achievement in Nigeria through e-learning technology - Adeshola Ayobami Adewoye; Ademola Samuel Sajuyigbe; Olatunji Fadeyi; Ojochile Fred Peter; Sunday Festus Olasupo; Matthew Olubayo Omotoso (Faculty of Social and Political Science, Universitas Airlangga, 2026)
This study examines the moderating role of e-learning technologies in the relationship between academic brain drain and student performance in Nigeria’s higher education. Quantitative research methods were used with an exploratory research design. Three hundred respondents were selected from three NUC-accredited institutions (University of Lagos, Lagos State University, and Covenant University). The Universities were chosen for their commitment to e-learning infrastructure. Through a multistage sampling procedure, the collected data were analyzed using path analysis (PA), which was implemented within structural equation modelling (SEM). The study reveals a significant negative relationship between the academic brain drain and university students’ academic performance due to the migration of the academic staff. Four forms of e-learning technology, namely video conferencing tools (VCT), digital libraries (DL), learning management systems (LMS), and online assessments (OA), in which VCT recorded the highest impact, were discovered to moderate between academic brain drain and student performance in Nigerian Higher Education institutions. This study concluded that, of the four forms of e-learning technology, it helps to align students’ academic progress in terms of exam results, cumulative GPAS, teaching results, learning outcomes, and successful completion of their courses, while their presence online increases a higher level of e-learning facility and training of faculty with digital teaching tools.